Wednesday

April 1, 2015

April 1, 2015

Posted by **Joe Bob** on Monday, May 7, 2012 at 9:23pm.

- Calculus -
**Steve**, Tuesday, May 8, 2012 at 5:08amsince ln(x) = -SUM[k>=1] (-1)^k * (x-1)^k/k

the integral is -SUM[k>=1] (-1)^k * (x-1)^(k-1)

**Answer this Question**

**Related Questions**

Math - Find the general expression of the kth nonzero term in the taylor series ...

Math - Find the general expression of the kth nonzero term in the taylor series ...

Calculus - Taylor #2 - Find the Taylor series for f(x) centered at the given ...

calculus - f(x) = 6x^2 -8x +3 how would I find the most general antiderivative ...

math - the "k"th term of a series, Sk=a 1-r^k/1-r, is the sum of the first "k" ...

calculus - how do i use a taylor series centered at some x value to approximate ...

Calculus Derivative- Taylor Series? - let f(x)= x/x-1 find f'(x) f ''(x) and a ...

Calculus - a) Find the Taylor series associated to f(x) = x^-2 at a = 1. Be sure...

Calculus - Please.... I need your help! I posted this question yesterday and no ...

calculus - Use multiplication of power series to find the first three non-zero ...